AWARENESS REGARDING DIFFERENT FAMILY PLANNING METHODS AMONG MARRIED WOMEN OF REPRODUCTIVE AGE GROUP IN URBAN SLUMS OF BERHAMPUR, ODISHA: A CROSS SECTIONAL STUDY - KIRAN, JWELL; NAYAK, LOMAPADA; SAHOO, SANJAYA KUMAR; KARMEE, NIVEDITA; SATAPATHY, DURGA MADHAB (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: To determine knowledge and practice of contraception and to find out the association between contraceptive practices and different variables. Methods: A cross-sectional, community-based study was conducted among 300 married women of 15–49 year age group of urban slums of Berhampur, Odisha, using a pretested and predesigned schedule. Results: Majority of women (93%) were aware of different types of FP methods but only 79.7% of females had known where the services are available. Health worker females (77.3%) act as the most influential source of information about contraceptive practices followed by the ASHA (71.6%). The contraceptive prevalence rate was 78.7%. Out of 236 Current users, temporary methods were being adopted by 65.3% and permanent methods by 34.7% respectively. Among the temporary method users, 24.1% of women used oral contraceptive pills, IUCD and injectables were being used by 6.4% each and condoms were being used by the partners of 28.4% of women as a means of contraception. Acceptance of family planning methods was significantly associated with variables such as increasing age, nuclear family, and level of literacy. Conclusion: The prevalence of contraceptive use was high among the study population, but the use of a modern and safe method of contraception was low. Continuous IEC activities by the service providers such as ASHAs, AWWs, and HWFs with support from the supervisor matters for better adherence to contraceptive methods.